The Effect of Mineral Trioxide Aggregate on the Periapical Tissues after Unintentional Extrusion beyond the Apical Foramen - Pradnya S. Nagmode; Archana B. Satpute; Ankit V. Patel; Pushpak L. Ladhe (Case Reports in Dentistry, 2016)
Introduction. Single-step apexification procedures using mineral trioxide aggregate (MTA) have been reported as favorable treatment options for teeth with an open apex, posing greater benefits compared to the other available medicaments. However, controlled apical placement of MTA is a challenging procedure to perform using orthograde approach. This case series describes the outcome of the unintentional extrusion of MTA into periradicular tissues during apexification, in three separate cases. Methods. Three adult patients reported to the Department of Conservative Dentistry and Endodontics for the management of maxillary incisors with open apices. After isolation, conventional access, and cleaning and shaping procedures, one-step MTA apexification was performed. On subsequent radiographs, a considerable amount of MTA was seen to be extruded in all the three cases. Results. During follow-up examination the teeth were seen to be asymptomatic in all cases and radiographically demonstrated repair of the periapical lesion. Conclusion. The results of these cases suggest that extrusion of MTA into the periapical tissues does not cause any detrimental effect, which could be attributed to the biologic properties of MTA.